The effects of the Directive on representative actions for the protection of the collective interest of consumers on the French group action regime - Maria José Azar-Baud (Revista Ítalo-Española de Derecho Procesal, 2020)
By transposing the Directive on representative actions for the protection of the collective interests of consumers by the 25th December 2022, all the Member States will be endowed with at least one form of collective redress. This paper analyses the Directive’s provisions that entail the need to introduce reforms in the French group action regime, as well as those outlined in the European text as recommendations that may constitute an opportunity to change the French state of affairs.